Practice, Knowledge, and Attitude of Health Care Providers regarding Cancer Pain Management: A National Survey - Jinmei Liu; Ming Zhang; Juan Luo; Jiyi Xie; Xu Chen; Hanxiang Wang; Shijun Li; Shengli Yang; Chunfen Peng; Liangle Yang; Bin Deng; Yu Zhang; et al. (Pain Research and Management)
Background. A lack of knowledge and inadequate practices of health care providers (HCPs) are the main obstacles to effective cancer pain management (CPM). The main objective of the study was to evaluate the CPM knowledge, CPM practice, and attitudes towards pharmacists’ participation and advanced methods in CPM of physicians, nurses, and pharmacists in China. Methods. An open online survey was adopted using social media software (WeChat) as the platform to conduct a nationwide survey of HCPs involved in CPM in public medical institutions at all levels in China from March to June 2019. Results. A total of 1279 physicians, 2267 nurses, and 1466 pharmacists participated in the survey. Among the three types of professionals, nurses had the highest level of practical ability (61.63 ± 28.99) and best attitudes towards pharmacists’ participation and advanced methods in CPM (72.05 ± 33.71) and physicians had the best mastery of CPM-related knowledge (69.60 ± 28.45), while pharmacists performed the worst in these three aspects (50.04 ± 26.69, 61.49 ± 28.95, and 62.07 ± 36.46, respectively). Only 19.69% of the hospitals had a pharmacist to tumor patient ratio ≥1 : 50. Hierarchical analysis showed that passing a good pain management (GPM) ward program and participating in advanced training had positive impacts on the scores of all three parts in the three professions (ptrend <0.05). Conclusions. HCPs’ levels of practice, knowledge, and attitudes towards pharmacists and advanced methods of CPM were average in China; however, pharmacists had the worst performance, which demonstrates a need for further improvement. Furthermore, GPM ward programs and advanced trainings are helpful for improving CPM levels.